2020
DOI: 10.1192/bjb.2020.44
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of doctors during the COVID-19 pandemic

Abstract: This article highlights the increased

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
250
1
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(277 citation statements)
references
References 59 publications
8
250
1
18
Order By: Relevance
“…During the early stages of the Covid-19 epidemic, many researchers reported the need to provide interventions to support the mental health of people affected by the Covid-19 crisis [ 15 , 16 , 19 , 87 , 88 ], in particular for healthcare workers [ 18 , 89 , 90 , 91 ] and patients with the Covid-19 infection [ 92 , 93 ]. For this purpose, many scholars suggested the use of mindfulness interventions [ 94 , 95 , 96 , 97 ]. However, studies assessing the impact of interventions that supported mental health in the early stages of the Covid-19 related crisis are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…During the early stages of the Covid-19 epidemic, many researchers reported the need to provide interventions to support the mental health of people affected by the Covid-19 crisis [ 15 , 16 , 19 , 87 , 88 ], in particular for healthcare workers [ 18 , 89 , 90 , 91 ] and patients with the Covid-19 infection [ 92 , 93 ]. For this purpose, many scholars suggested the use of mindfulness interventions [ 94 , 95 , 96 , 97 ]. However, studies assessing the impact of interventions that supported mental health in the early stages of the Covid-19 related crisis are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported about the importance of team climate (Maunder et al 2003(Maunder et al , 2004(Maunder et al , 2006Khee et al 2004;Lee et al 2005) because it can reduce the negative effects of social isolation (Maunder et al 2003(Maunder et al , 2004(Maunder et al , 2006. In fact, also during the COVID-19 outbreak many HCWs decided to isolate themselves to not infect their families (Lee et al 2005;Fichtel and Kaufman 2020).…”
Section: Person-directed Strategiesmentioning
confidence: 99%
“…This unpleasant emotion can be amplified by social disparities as well as by the spread of stigma associated with COVID-19, affecting not only those newly diagnosed with the disease but also health care providers. As in many cases, the source of COVID-19 cannot be easily traced, and social stigma may arise toward people who have the most contact with patients (Galbraith et al, 2020). Thus, nurses, doctors, and health care providers as a whole may be perceived by other people as "unsafe" because of their job and thereby become victims of avoidant behaviors.…”
Section: The Shame Of Covid-19mentioning
confidence: 99%